2021
DOI: 10.1021/acs.jmedchem.1c00701
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Notum Covalent Inhibition

Abstract: The carboxylesterase Notum hydrolyzes a palmitoleate moiety from Wingless/Integrated(Wnt) ligands and deactivates Wnt signaling. Notum inhibitors can restore Wnt signaling which may be of therapeutic benefit for pathologies such as osteoporosis and Alzheimer’s disease. We report the identification of a novel class of covalent Notum inhibitors, 4-(indolin-1-yl)-4-oxobutanoate esters. High-resolution crystal structures of the Notum inhibitor complexes reveal a common covalent adduct formed between the nucleophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 55 publications
(94 reference statements)
3
28
0
Order By: Relevance
“…Calculations involving the 6-311+g(2d,2p) basis set predicted a more stable IC-2 structure, and the overall acylation process turned out to be an exergonic process. This result is in agreement with the experimental results 14 in that the crystal structure of Notum together with inhibitor 1 resulted in the irreversible covalent adduct, which correspond to an IC-2 structure. Of all the calculated complexes, IC-2 is predicted to be the most stable species.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Calculations involving the 6-311+g(2d,2p) basis set predicted a more stable IC-2 structure, and the overall acylation process turned out to be an exergonic process. This result is in agreement with the experimental results 14 in that the crystal structure of Notum together with inhibitor 1 resulted in the irreversible covalent adduct, which correspond to an IC-2 structure. Of all the calculated complexes, IC-2 is predicted to be the most stable species.…”
Section: Resultssupporting
confidence: 92%
“…This observation is in agreement with the fact that methyl ester 1 acts as an irreversible inhibitor by forming a covalent adduct as a result of transesterification between 1 and Ser232. 14 On the basis of the crystal structure of this adduct ( Figure 2 ), it was suggested that the deacylation process is unfavorable because of the strong hydrophobic interactions and the unfavorable position of the active site water molecule for the nucleophilic addition step. It was also stated that the nucleophilic attack is hindered, since the angle between the O atom of the water molecule with carbonyl C and O atoms is 87° in the crystal structure ( Figure 2 ); however, the same angle is 114° for the native substrate O -palmitoleate ester.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations